Potensi Pengembangan Industri di Kabupaten Dairi - Irfan Ruhaimi; Angelica Natasya Situmorang; Ahyana Isma; Mahdariani Mahdariani; Qamara Aulia Ananda (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Dairi Regency has a favorable geographical location, Sidikalang is the capital of Dairi Regency and has enormous industrial potential. The purpose of this study is to determine the potential for industrial development in Dairi Regency. The research method used is a qualitative research method that is library research using books and other literature as the main object. The results of the study show that geographical conditions, climate, and natural resources support various types of plants. The leading commodities are curly chilies, shallots, ginger, turmeric, corn, paddy fields, durian, Siamese oranges, Arabica coffee, and Robusta coffee. The potential for developing the fisheries industry with a focus on tilapia, carp, catfish, and jurung. The potential for developing tourism with ecotourism; trekking, mountain biking, observing flora and fauna, relaxing at Lake Toba. Agrotourism: visiting coffee, tea, orange plantations, learning about cultivation, then farming. Culinary and cultural tourism; art and cultural performances, cooking classes, culinary tourism. Travel history; King Silahi Sabungan Tomb Monument, Dairi Faith Tourism Park, Tao Silalahi. Religious tourism; Sidikalang Old Church, Sidikalang Grand Mosque.